A different approach to the performance management in tourism sector conformity between individual and organizational performances - Bakkalbaşı, İhsan Oğuz (My University, 2003)
Adı ve Soyadı : İhsan Oğuz Bakkalbaşı Kamu Yönetimi Human Resource Management & Development Yard. Doç. Dr. Tuğrul Savaş Tez Türü ve Tarihi : Yüksek Lisans-Ağustos 2003 Performans Yönetimi, Müşterilerin Sürece Dahil Edilmesi

Turizm sektörünün ürünü hizmettir. Bu hizmet müşterilerin gezileri sırasında, karşıladıkları barınma, yeme-içme, dinlenme, eğlenme gibi ihtiyaçlarını nasıl temin ettikleridir. Dolayısıyla turizm sektöründe çalışanların, hizmet icra ederken, takındıkları davranış biçimi müşteri tatminini sağlayacak biçimde olmalıdır. Diğer bir deyişle, müşteri tatminini sağlayacak davranışlar, çalışanların performans değerlendirmesine baz oluşturabilir. Bu değerlendirmeyi de en iyi müşteriler yapar. Önemli olan müşterilerin bu kriterlerle yapacağı değerlendirmeyi, bireylerin performans ölçümlerine indirgemek veya bunlarla birleştirmektir. İşte bu çalışma bunun nasıl olabileceğini açıklamaya çalışmaktadır. Name and Surname : İhsan Oğuz Bakkalbaşı Fields : Political Science & Administration Program : Human Resource & Development Management Supervisor : Yard. Doç.Dr. Tuğrul Savaş Degree Awarded and Date : Master - August 2003 Performance Management, Involving The Clients Into The Process ABSTRACT The product of the tourism sector is the service. This product, the service is that how the tourists satisfy their needs, such as billeting, food & beverage, resting, having fun; during their journey. Then the behaviors on the job of the employees should accomplish the clients' content. In other words, the behaviors, which ensure the clients' content, would be the base of the performance appraisal of the employees. The best appraisers would be the clients. The point is to convert these criteria to individual performance appraisal or to unify these criteria with it. Hence, this working endeavors to describe how it can be realized.
Keywords: Performans Yönetimi